Treatment and prevention of malaria in pregnancy in the private health sector in Uganda: implications for patient safety. (December 2016) - Mbonye, Anthony; Buregyeya, Esther; Rutebemberwa, Elizeus; Clarke, Siân; Lal, Sham; Hansen, Kristian; Magnussen, Pascal; LaRussa, Philip
Abstract Background Malaria in pregnancy is a major public health problem in Uganda; and it is the leading cause of anaemia among pregnant women and low birth weight in infants. Previous studies have noted poor quality of care in the private sector. Thus there is need to explore ways of improving quality of care in the private sector that provides almost a half of health services in Uganda. Methods A survey was conducted from August to October 2014 within 57 parishes in Mukono district, central Uganda. The selected parishes had a minimum of 200 households and at least one registered drug shop, pharmacy or private clinic. Data was collected using a structured questionnaire targeting one provider who was found on duty in each selected private health facility and consented to the study. The main variables were: provider characteristics, previous training received, type of drugs stocked, treatment and prevention practices for malaria among pregnant women. The main study outcome was the proportion of private health facilities who prescribe treatment of fever among pregnant women as recommended in the guidelines. Results A total of 241 private health facilities were surveyed; 70.5 % were registered drug shops, 24.5 % private clinics and 5.0 % pharmacies. Treatment of fever among pregnant women in accordance with the national treatment guidelines was poor: 40.7 % in private clinics, decreasing to 28.2 % in drug shops and 16.7 % at pharmacies. Anti-malarial monotherapies sulphadoxine-pyrimethamine and quinine were commonly prescribed, often without consideration of gestational age. The majority of providers (>75 %) at all private facilities prescribed SP for intermittent preventive treatment but artemisinin-based combination therapy was prescribed: 8.3, 6.9 and 8.3 % respectively at drug shops, private clinics and pharmacies for prevention of malaria in pregnancy. Few facilities had malaria treatment guidelines; (44.1 % of private clinics, 17.9 % of drug shops, and 41.7 % at pharmacies. Knowledge of people at risk of malaria, P = 0.02 and availability of malaria treatment guidelines, P = 0.03 were the factors that most influenced correct treatment of fever in pregnancy. Conclusion Treatment of fever during pregnancy was poor in this study setting. These data highlight the need to develop interventions to improve patient safety and quality of care for pregnant women in the private health sector in Uganda.